Pengukuran Morfometrik Sapi Peranakan Ongole dan Kerbau Jantan dengan Metode Citra Digital (MORPHOMETRIC MEASUREMENT OF MALE ONGOLE CROSSBRED CATTLE AND BUFFALO BY DIGITAL IMAGE ANALYSIS ) - Hilmawan, Fiqy; Nuraini, Henny; Priyanto, Rudy; Putra, Bramada Winiar (Jurnal Veteriner, 2017)
The objectives of this study were to compare the methods of animal morphometricmeasurementsusing manual and digital image analysis methods on the identify of ongole crossbred cattle and buffalo. Asmany as38 maleongole crossbred cattle and 44 male buffalos were used in this study. Fifteen bodyparameters were examined and analyzed and the data obtained were analyzed by t-student to determinethe differences between of two measurement methods. The morphometric measurement of ongole crossbredcattle and buffalo by manual was not significantly different (P>0.05) as compared to that of by digitalimaging. Therefore the digital imaging analysis method could be used as an alternative morphometricmeasurement forlarge ruminant animalal such as cattle and buffalos. Based on body morphometric bydigital image analysis showed that ongole crossbred cattle has ossa radius-ulna, os metacarpale, ossatibia fibulla, os metatarsale, hip height and body height longer than buffalo (P<0,05). Depth chest ofbuffalo deeper than ongole crossbred cattle (P<0,05). Body measurement of livestock animal by digitalanalysis method could be applied as it has similar accuracy with the manual method. Ongole crossbredcattle has good potency as beef cattle because it has higher body size proportion than buffalo.
Keywords: ongole crossbred cattle; buffalo; animal morphometric; digital image analysis